2016
DOI: 10.1186/s12916-016-0709-0
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and type 2 diabetes in sub-Saharan Africans – Is the burden in today’s Africa similar to African migrants in Europe? The RODAM study

Abstract: BackgroundRising rates of obesity and type 2 diabetes (T2D) are impending major threats to the health of African populations, but the extent to which they differ between rural and urban settings in Africa and upon migration to Europe is unknown. We assessed the burden of obesity and T2D among Ghanaians living in rural and urban Ghana and Ghanaian migrants living in different European countries.MethodsA multi-centre cross-sectional study was conducted among Ghanaian adults (n = 5659) aged 25–70 years residing i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
170
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 154 publications
(180 citation statements)
references
References 28 publications
8
170
2
Order By: Relevance
“…Some studies in Ghana have alluded to the fact that socioculturally, a large body size among females is perceived as a sign of affluence [27], and women with higher education are likely to be affluent and have more exposure to energy-dense foods. The observed association of sedentary lifestyle with higher BMI among men and women is largely consistent with other studies both outside [1] and within Africa [39,45] and Ghana [41,42]. …”
Section: Discussionsupporting
confidence: 90%
“…Some studies in Ghana have alluded to the fact that socioculturally, a large body size among females is perceived as a sign of affluence [27], and women with higher education are likely to be affluent and have more exposure to energy-dense foods. The observed association of sedentary lifestyle with higher BMI among men and women is largely consistent with other studies both outside [1] and within Africa [39,45] and Ghana [41,42]. …”
Section: Discussionsupporting
confidence: 90%
“…Previous studies in this rural population have reported higher BMIs in females, with an age-adjusted prevalence of obesity of 26% in females aged 15 and older compared to 7% in similarly aged males [17] and a 24.6% higher prevalence of obesity in females in those over 50 years [18]. Similar differences were evident in rural Ghana where the prevalence of obesity in women was seven times that in men [24]. The sex disparity in obesity appears independent of urbanicity with females in rural and peri-urban Uganda being 4.3 times as likely to be obese as males [25] and the prevalence of obesity in females 20–75 years of age in urban Cameroon being 4 times that of their male counterparts [26].…”
Section: Discussionsupporting
confidence: 65%
“…We also observed marked differences in BMI, which could partly explain the differences in CVD risk among these populations because a recent study that explored BMI among Ghanaian migrants and their home counterparts found increasing prevalence of obesity, with a rising gradient from rural Ghana to urban Ghana to Europe. 23 Other lifestyle and behavioral changes after migration have been cited as possible explanation for increased CVD risk among migrant populations. In this study, we observed differences in physical activity and psychosocial stress between the migrants and their home counterparts.…”
Section: Discussion Of Key Findingsmentioning
confidence: 99%
“…21 The equations are derived using pooled data from ethnically and geographically diverse community-based cohorts, permitting the creation of sex-and ethnic-specific equations for non-Hispanic White American and Black women and men. 22 Because most studies on CVDs among African migrant populations have focused on individual risk factors, this study, as part of the RODAM study (Research on Obesity and Diabetes Among African Migrants), 23,24 sought to (1) assess the potential role of migration on CVD risk by assessing the differences in 10-year estimated CVD risk among nonmigrant Ghanaians living in rural and urban Ghana and Ghanaian migrants living in 3 different European countries using the PCE algorithms and (2) assess the modifiable risk factors that predispose them to poor CVD outcomes in their host countries.…”
Section: Boateng Et Al Cardiovascular Disease Risk Among Ghanaian Migmentioning
confidence: 99%